Christ's Prophetic Plans A Futuristic Premillennial Primer - MacArthur, John; Richard Mayhue (Chicago Moody Publishers, 2012)
John MacArthur and Richard Mayhue help to provide a clear and convincing Biblical explanation for the interpretive approach to Scripture that results in a knowable futuristic view of Christ's millennial reign on earth. Christ's Prophetic Plans also help
Keywords: Millennialism